2022
DOI: 10.3390/polym14071423
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Compressive Strength of Fly Ash Geopolymer Concrete by an Optimised Neural Network Model

Abstract: This article presents a regression tool for predicting the compressive strength of fly ash (FA) geopolymer concrete based on a process of optimising the Matlab code of a feedforward layered neural network (FLNN). From the literature, 189 samples of different FA geopolymer concrete mix-designs were collected and analysed according to ten input variables (all relevant mix-design parameters) and the output variable (cylindrical compressive strength). The developed optimal FLNN model proved to be a powerful tool f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The ANN model accurately predicts absorption rate as a function of binder content, basal fiber content, compressive strength, and changes in concrete mass [40]. Furthermore, other studies reveal that fly ash-based geopolymers utilizing a developed Neural Network model algorithm are potent tools for predicting geopolymer compressive strength [41]. Machine learning techniques applied to predict concrete compressive strength based on cellulose nanofibers yield R 2 >0.72, MAPE ≤ 0.1, and MAE ≤ 5, aligning with the standard of R 2 values exceeding 0.60 [42].…”
Section: Table 1 the Comparison Of Modelling Results Based On Ann Par...mentioning
confidence: 95%
“…The ANN model accurately predicts absorption rate as a function of binder content, basal fiber content, compressive strength, and changes in concrete mass [40]. Furthermore, other studies reveal that fly ash-based geopolymers utilizing a developed Neural Network model algorithm are potent tools for predicting geopolymer compressive strength [41]. Machine learning techniques applied to predict concrete compressive strength based on cellulose nanofibers yield R 2 >0.72, MAPE ≤ 0.1, and MAE ≤ 5, aligning with the standard of R 2 values exceeding 0.60 [42].…”
Section: Table 1 the Comparison Of Modelling Results Based On Ann Par...mentioning
confidence: 95%
“…Based on the pioneering literature [ 15 , 19 , 22 , 26 ] and previous experience [ 27 ], the alkaline activator solution (AAS) was fixed at probable optimum controlling factors: molarity of SH = 16 M, SS/SH = 2.0, and w/GPS = 0.2, where w/GPS is the water (w) to geopolymer-solid (GPS) ratio. The WFS was wet by the amount of water (w extra ) to reach the optimum moisture content (OMC).…”
Section: Methodsmentioning
confidence: 99%
“…The annual CO 2 emissions from OPC production are estimated to be around 4 billion tons [18,24]. In the context of energy consumption and the decarbonization process applied in the conversion of limestone, about 1 ton of CO 2 is released per ton of cement production [25][26][27][28][29][30]. The International Energy Agency (IEA) reported that these emissions account for 5-8% of total CO 2 emissions globally [31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%